Validation of E-Module Based on Argument-Driven Inquiry using 3D Page Flip Professional to Improve Students' Generic Science, Critical Thinking and Scientific Argumentation Abilities - Amalia Syuzita; Susilawati Susilawati; AA Sukarso (Jurnal Penelitian Pendidikan IPA, 2023)
The development of E-module based on Argument-Driven Inquiry using 3D Pageflip Professional has been carried out to improve the generic science skills, critical thinking and scientific argumentation of students. This development aims to describe the validation of e-module teaching materials that are suitable for use in learning activities. The development model design used is 4D which consists of definition, design, development and dissemination stages. This research is limited to the development stage. Validation activities have been completed in the development process. The validity of the e-module was assessed by 3 competent experts who are competent at Mataram University. In addition to the validity of the e-module, there are several learning tools that are assessed for validity to support the quality of the e-module developed. Some of these learning tools include syllabus, lesson plans, worksheets, test instruments for science generic ability, critical thinking and scientific argumentation. The results show that e-module based on Argument-Driven Inquiry assisted by 3D Pageflip professional can be used in science learning activities at school